The Philosophical Bases of Nursing Knowledge Development - Joel Rey Ugsang Acob (Aloha International Journal of Health Advancement (AIJHA), 2018)
Scientific evidence can accumulate to support or rebut theoretical contention or provide the basis for suggesting modifications in a nursing theory only through repeated and rigorous research. Nursing has evolved from periods of being in a traditional observation to scientific patterns of doing nursing care. The early works paved the way to recognize the complicated and yet systematic process of human interactions and documented that the pluralistic understanding of science emphasizes the construction of scientific models and nursing endeavors that are appropriate for a more effective response to the need of health. Further, nurses have to identify his or her working philosophy for the efffective and efficient delivery of care to clienteles. Keywords: Nursing, Development